2000
DOI: 10.1128/aac.44.10.2911-2914.2000
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Antibiotic Resistance Mediated by Structurally Related IncL/M Plasmids Carrying an Extended-Spectrum β-Lactamase Gene and a Class 1 Integron

Abstract: A conjugative IncL/M plasmid (pSEM) conferring resistance to gentamicin, amikacin, kanamycin, sulfonamides, and expanded-spectrum cephalosporins was found in pathogenic strains of Salmonella enterica serotype Typhimurium. Resistance to aminoglycosides was encoded by a sul1-type class 1 integron (In-t3). An extendedspectrum beta-lactamase gene, bla SHV-5 , was identified 3.5 kb downstream of the integrase (intI1) gene of In-t3. Nucleotide sequence analysis of the 5.3-kb bla SHV-5 -In-t3 region of pSEM highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 27 publications
(29 reference statements)
6
74
0
2
Order By: Relevance
“…Such wide resistance spectra of ESBL producers, including resistance to drugs such as sulfonamides, trimethoprim and aminoglycosides, have been observed by many others (Jett et al, 1995;Villa et al, 2000;Subha et al, 2001). One study reported that ciprofloxacin resistance and ESBL production in Klebsiella pneumoniae are closely associated (Paterson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Such wide resistance spectra of ESBL producers, including resistance to drugs such as sulfonamides, trimethoprim and aminoglycosides, have been observed by many others (Jett et al, 1995;Villa et al, 2000;Subha et al, 2001). One study reported that ciprofloxacin resistance and ESBL production in Klebsiella pneumoniae are closely associated (Paterson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other Indian studies, the majority of our ESBL/AmpC-producing E. coli exhibited a high level of resistance towards quinolone (93.1 %) and FQ (75 %), which would have therapeutic implications (Baby Padmini et al, 2008). Several reports have documented a strong correlation between qnrA prevalence and ESBL positivity in E. coli isolates, especially the CTX-M type (Jacoby et al, 2003;Mammeri et al, 2005;Lavigne et al, 2006), which could frequently be due to the presence of these resistance determinants on mobile genetic elements (Jacoby & Sutton, 1991;Partridge et al, 2001;Preston et al, 2003;Villa et al, 2000;Wang et al, 2003 The virulence potential and multiple drug resistance observed among the E. coli of non-B2 phylogroups further strengthens the claim that horizontal gene transfer might play a major role in the emergence of drug resistance among these originally avirulent/less virulent strains which can no longer be called 'innocent bystanders'. Also, prior exposure to 3G cephalosporins/FQs probably serves as a driving force for the selection of multidrug-resistant isolates primarily of endogenous origin to establish UTI among HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other Indian studies, the majority of our ESBL/AmpC-producing E. coli exhibited a high level of resistance towards quinolone (93.1 %) and FQ (75 %), which would have therapeutic implications (Baby Padmini et al, 2008). Several reports have documented a strong correlation between qnrA prevalence and ESBL positivity in E. coli isolates, especially the CTX-M type (Jacoby et al, 2003;Mammeri et al, 2005;Lavigne et al, 2006), which could frequently be due to the presence of these resistance determinants on mobile genetic elements (Jacoby & Sutton, 1991;Partridge et al, 2001;Preston et al, 2003;Villa et al, 2000; Wang et al, 2003). In our study, of the 34 isolates that possessed bla CTX-M , 30 (88.2 %) were FQ …”
mentioning
confidence: 99%
“…The pSEM plasmid was identified in 1997 in S. typhimurium strains isolated from children in Albania (Villa et al, 2000), while pACM1 was isolated from K. oxytoca strains responsible of a nosocomial outbreak in the USA (Preston et al, 1997;Preston et al, 1999). Both plasmids belonged to the same IncL/M group and conferred resistance to expanded-spectrum cephalosporins by the blaSHV-5 gene.…”
Section: Importance Of Plasmids In the Dissemination Of Resistance Inmentioning
confidence: 99%
“…During the last decade, infections caused by S. enterica carrying ESBLs have been reported, and most of the ESBL-producing strains were found to carry plasmids encoding the blaTEM-1, and blaSHV-1 gene derivatives (Hammani et al, 1991;Morosini et al, 1995;Tassios et al, 1997;Villa et al, 2000;Mulvey et al, 2003).…”
Section: Importance Of Plasmids In the Dissemination Of Resistance Inmentioning
confidence: 99%